2009
DOI: 10.1002/hon.896
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of rituximab on CD5‐positive and CD5‐negative diffuse large B‐cell lymphoma

Abstract: The prognosis of diffuse large B-cell lymphoma (DLBCL) has improved markedly in recent years of rituximab era. The prognosis of de novo CD5-positive DLBCL is reported to be poor, but the effect of rituximab on this type of lymphoma remains unclear. To investigate the effect of rituximab on CD5-positive DLBCL, we collected DLBCL patients and analysed prognostic factors. A total of 157 patients with DLBCL who were immunophenotyped with flow-cytometry (FCM) and treated with chemotherapy were subjected to analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 48 publications
2
30
0
3
Order By: Relevance
“…CD5-positive DLBCL are typically ABC [42, 48], show recurrent gains of 16p and losses of 1p and of 9q21 [36, 49], the latter being involved in chemoresistance [37], and display downregulation of extracellular matrix-related genes and upregulation of neurological function-related genes [48]. Addition of rituximab to CHOP improved the survival of CD5-positive DLBCL patients [50]; however, similarly to our results, the outcome of these patients is still significantly poorer compared to CD5-negative DLBCL patients [51], and the rate of CNS involvement seems not to be lowered by rituximab [52]. A recent very large retrospective report on 879 R-CHOP-treated DLBCL cases convincingly showed CD5 to be an IPI (and bcl2 and pSTAT3)-independent prognosticator in DLBCL as well [53] and pointed out distinct clinico-pathological peculiarities of such patients such as increased age, bone marrow spread, poor performance status, and B symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…CD5-positive DLBCL are typically ABC [42, 48], show recurrent gains of 16p and losses of 1p and of 9q21 [36, 49], the latter being involved in chemoresistance [37], and display downregulation of extracellular matrix-related genes and upregulation of neurological function-related genes [48]. Addition of rituximab to CHOP improved the survival of CD5-positive DLBCL patients [50]; however, similarly to our results, the outcome of these patients is still significantly poorer compared to CD5-negative DLBCL patients [51], and the rate of CNS involvement seems not to be lowered by rituximab [52]. A recent very large retrospective report on 879 R-CHOP-treated DLBCL cases convincingly showed CD5 to be an IPI (and bcl2 and pSTAT3)-independent prognosticator in DLBCL as well [53] and pointed out distinct clinico-pathological peculiarities of such patients such as increased age, bone marrow spread, poor performance status, and B symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…Bone marrow (BM) involvement (28%) and central nervous system (CNS) relapse (12.7%) are increased in CD5 + DLBCL patients [14, 16, 20]. However, in one study CD5 expression status did not correlate with prognosis by univariate or multivariate analysis, either in all patients or in rituximab-treated patients [18]. The effect of adding rituximab to CHOP on survival of CD5 + DLBCL patients also has been inconsistent in different studies [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study CD5 expression status did not correlate with prognosis by univariate or multivariate analysis, either in all patients or in rituximab-treated patients [18]. The effect of adding rituximab to CHOP on survival of CD5 + DLBCL patients also has been inconsistent in different studies [18-20]. In Western countries, a few cases of de novo CD5 + DLBCL have been reported [21, 22], and a morphologic and immunophenotypic study of 13 cases of de novo CD5 + DLBCL showed heterogeneous features [23].…”
Section: Introductionmentioning
confidence: 99%
“…Five percent to 10% of DLBCL are CD5-positive. This marker identifies a subset of ABC-type DLBCL characterized by advanced stage of disease at diagnosis, aggressive clinical course, and resistance to rituximab therapy [45]. BCL2 positivity (a condition associated with poor prognosis) and lack of CD10 are more frequently observed within CD5 + DLBCL.…”
Section: Diffuse Large B-cell Lymphoma Nosmentioning
confidence: 99%